Molecular structure, UV–Visible spectra and other molecular properties of (E)-2-(2-hydroxy-5-methoxybenzylidene)hydrazinecarbothioamide and its n-methyl variant by using DFT methods - K. Srishailam; L. Ravindranath; Gaddam. Ramesh; D. Praveena; Sunil kumar V; Danikonda.Suresh Kumar; S. Muthu; G.Ramana Rao (Results in Chemistry)
The primary aim of the present work is to make a theoretical evaluation of electronic structure for 2-(2-hydroxy-5-methoxybenzylidene)hydrazinecarbothioamide (HMHC) and 2-(2-hydroxy-5methoxybenzylidene)-N-methylhydrazinecarbothioamide (HMNHC). Subsequently, we also aim to compute molecular electronic properties such as FMO, NBO, NLO, MESP and Fukui functions to compare them with their corresponding experimental values, wherever available. To this end we made geometry optimization for HMHC and HMNHC using DFT/B3LYP/6–311++G(d,p) formalism. The computations identified the existence of both intra-molecular and bifurcated intra-molecular hydrogen bonds in both the molecules. Time-dependent density functional theory (TD-DFT) was employed to simulate Ultra-Violet spectra for both HMHC and HMNHC in order to substantiate experimental spectra in a solution of dimethyl formamide. For the two compounds under investigation, specific global reactivity descriptors were estimated with the help of frontier molecular orbital (FMO) analysis to understand the origin of UV–Vis spectra. Nonlinear optical (NLO) profile, for each of the two molecules, was computed, with in the frame work of the DFT/B3LYP/6–311++G(d,p) formalism to determine their utility for NLO applications. NBO analysis of hyper conjugate interactions made it possible to interpret the molecules NLO behavior in terms of intramolecular charge transfer (ICT). The reactive sites around the molecules were identified using Fukui function investigations. It is heartening to note that all parameters computed in this work for both HMHC and HMNHC compare reasonably well with their available experimental values.